Analisis Implementasi Peningkatan Kualitas Pendidikan Melalui Standarisasi Laboratorium di SMAN 5 Jember - ., Septia Rachma Wulansari; ., Moh. Rifki Hariyanto; ., Nur Elizah; ., Renisa Kusuma Dewi; ., Lailiatul Istianah; ., Lailatul Nuraini (Jurnal Pendidikan, Sains Dan Teknologi, 2023)
This study was conducted with the aim of analyzing the implementation of Physics Laboratory Standards at SMA Negeri 5 Jember. The research method used in this research is descriptive method with qualitative approach. Data collection was done through questionnaires and interviews with the head of the laboratory and also with physics teachers. In addition, data collection is also through direct laboratory observation, interviews through the head of the laboratory assistant, and document analysis such as guidebooks and the use of tools and materials in the laboratory. In this study, the results showed that the infrastructure facilities in the laboratory showed an average percentage of 90% with a very good classification. The results of standardization for tools and materials got an average of 68% with a good classification. Furthermore, the standardization of laboratory personnel with a very good classification on average 90%. In the standardization of security, maintenance and supervision of the laboratory gets an average percentage of 91% with a very good classification. The last is the standardization of services gets an average percentage of 100% with a very good classification. Overall, the laboratory at Jember 5 Public School has good standardization, but there is a need to improve the quality of these laboratory facilities so that they can support the learning process better.